2017
DOI: 10.46357/bcnaturais.v12i3.86
|View full text |Cite
|
Sign up to set email alerts
|

Proteases ácidas de cogumelo comestível da Amazônia para aplicabilidade industrial

Abstract: As proteases constituem um grupo de enzimas que apresentam elevada aplicabilidade em diversos setores industriais, sendo obtidas de fontes animais, vegetais e microbianas. Entre os fungos, os cogumelos têm se destacado como fonte de proteases com potencial biotecnológico. O objetivo deste trabalho foi investigar a produção de proteases por cogumelos, utilizando a fermentação em meio líquido. A cultura matriz foi preparada em ágar batata dextrose, acrescida de extrato de levedura 0,5% (p/v), e o bioprocesso foi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
1
0
3
Order By: Relevance
“…Thus, it can be inferred that the cultivation of G. lucidum under submerged fermentation in a non-agitated condition favors the process of protein recovery from mycelial biomass, resulting in protein extracts with a higher content of soluble proteins. Martim et al (2017) when working with submerged fermentation of G. lucidum at 150 rpm, in a culture medium similar to experiment 4 of the present work, but supplemented with gelatin, found a proteolytic activity of 23.5 U.mL -1 . Thus, it is suggested that the cultivation of G. lucidum in submerged fermentation in non-agitated condition is more efficient in the recovery of proteases.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, it can be inferred that the cultivation of G. lucidum under submerged fermentation in a non-agitated condition favors the process of protein recovery from mycelial biomass, resulting in protein extracts with a higher content of soluble proteins. Martim et al (2017) when working with submerged fermentation of G. lucidum at 150 rpm, in a culture medium similar to experiment 4 of the present work, but supplemented with gelatin, found a proteolytic activity of 23.5 U.mL -1 . Thus, it is suggested that the cultivation of G. lucidum in submerged fermentation in non-agitated condition is more efficient in the recovery of proteases.…”
Section: Discussionsupporting
confidence: 77%
“…--------------------Concentration (mM)------------------------------------Relative activity (%) ± SD----------------- been identified as being able to increase the stability due to reduced enzymatic autolysis (ALLPRESS et al 2002). MARTIM et al (2017), analyzing the effect of inhibitors on the proteolytic activity of Pleurotus albidus, observed the presence of serine and cysteine proteases in the crude extract of the fungus. The reduction of protease activity by reducing agents indicated that disulfide bonds are important to maintain the active conformation of these enzymes.…”
Section: Saltsmentioning
confidence: 99%
“…Para determinação do pH ótimo, a atividade proteolítica foi determinada a 25 °C em diferentes valores de pH, utilizando-se o substrato de azocaseína 1% (p/v) diluída em solução tampão composta por acetato de sódio (pH 5,0 e 6,0), Tris-HCl (pH 7,0 e 8,0), Glicina-NaOH (pH 9,0 e 10) (Martim, et al, 2017).…”
Section: Determinação Do Efeito Do Ph E Do Efeito Da Temperatura Na A...unclassified
“…Para determinação da temperatura ótima de atividade das proteases, utilizou-se temperaturas de 30-80 °C (Martim, et al, 2017).…”
Section: Determinação Do Efeito Do Ph E Do Efeito Da Temperatura Na A...unclassified